Burden and Associated Factors of Tuberculosis Among Household Contacts of Sputum Positive Tuberculosis Patients of Aligarh - Simon Jude; Ali J. Abedi; Saira Mehnaz; Mohammad Shameem (Indian Journal of Community Medicine)
Background: Engaging patients in healthcare for diagnosis and treatment through active case-finding, which is initiated by healthcare providers, involves methodically searching for tuberculosis in individuals who may not seek medical attention otherwise. Active case finding provides a promising opportunity to identify additional undetected cases of tuberculosis within the community. The current study aimed at evaluating household contact tracing of Tuberculosis among the household contacts of pulmonary TB cases who were recently diagnosed, as well as to identify risk factors in both household contacts and index cases that contribute to the transmission of TB within households. Materials and Method: This cross-sectional study, which was conducted within the community, focused on the household contacts of recently diagnosed patients of Pulmonary Tuberculosis (TB) who were confirmed through microbiological testing. These patients were registered at Tuberculosis Units (TUs) of JNMC and Jawan of Aligarh district, West U.P. The investigator conducted visits to each household and met with both the index case and their corresponding household contacts to establish rapport and gather necessary information. Results: Within this investigation, a total of 103 individuals who tested positive for sputum smear were identified as index cases, alongside 405 household contacts of these index cases. The predominant symptom observed in household contacts who tested positive during the screening process was a cough, with fever following closely behind. Among the 405 household contacts examined, 54 individuals (13.3%) exhibited symptoms associated with Tuberculosis. Further investigation revealed that 11 of these individuals (20.37%) tested positive for tuberculosis. The total prevalence of tuberculosis cases among household contacts was determined to be 2.72%. Conclusion: The present research affirms that conducting contact screening for households of active TB cases is a comparatively feasible and beneficial strategy that could result in prompt diagnosis and initiation of treatment for active TB, thereby diminishing the severity of the disease and lowering the rate of transmission. Also, it can help to improve TB-related health effects, social and economic implications, and treatment outcomes in the index cases.